2012
DOI: 10.4103/0976-3147.98205
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intracerebral hemorrhage: Clinical and computed tomography findings in predicting in-hospital mortality in Central Africans

Abstract: Background and Purpose:Intracerebral hemorrhage (ICH) constitutes now 52% of all strokes. Despite of its deadly pattern, locally there is no clinical grading scale for ICH-related mortality prediction. The first objective of this study was to develop a risk stratification scale (Kinshasa ICH score) by assessing the strength of independent predictors and their association with in-hospital 30-day mortality. The second objective of the study was to create a specific local and African model for ICH prognosis.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
(47 reference statements)
2
27
0
Order By: Relevance
“… 0·810 (0·033) Tshikwela [ 36 ] 2012 Black hypertensive primary ICH Score Discharge GCS, ICH volume, left hemisphere involved. Tshikwela´ [ 36 ] 2012 Black hypertensive primary ICH Score Discharge Gender, GCS, midline shift. Tuhrim [ 23 ] 1999 Primary supratentorial ICH managed medically Equation 30 days GCS, ICH volume, pulse pressure, hydrocephalus, and IVH volume.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 0·810 (0·033) Tshikwela [ 36 ] 2012 Black hypertensive primary ICH Score Discharge GCS, ICH volume, left hemisphere involved. Tshikwela´ [ 36 ] 2012 Black hypertensive primary ICH Score Discharge Gender, GCS, midline shift. Tuhrim [ 23 ] 1999 Primary supratentorial ICH managed medically Equation 30 days GCS, ICH volume, pulse pressure, hydrocephalus, and IVH volume.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies included further specifications for patient inclusion namely age [ 12 ], cerebral amyloid related angiopathy [ 13 ], deep location [ 14 17 ], lobar location [ 18 ], supratentorial bleeds [ 16 , 19 33 ], presence of intraventricular hemorrhage [ 16 , 34 , 35 ], African ethnicity [ 36 ], non-comatose patients [ 22 , 37 ], comatose patients [ 38 ], medically treated patients [ 22 25 , 27 , 33 , 38 40 ], surgically treated patients [ 21 ], oral anticoagulant related bleeds [ 41 ], hypertensive patients [ 19 , 36 ], and dialysis patients [ 40 ]. The majority of studies ( n = 40) recruited patients from hospitals or emergency rooms [ 10 14 , 16 22 , 26 , 29 31 , 36 , 40 61 ] but nine studies recruited patients from intensive care units [ 24 , 28 , 32 , 33 , 35 , 38 , 62 64 ], three studies recruited patients from stroke units [ 34 , 37 , 65 ], six studies recruited patients from neurology/neurosurgery departments [ 15 , 25 , 27 , 39 , 66 , 67 ], and one study recruited patients from both an intensive care unit and a stroke unit [ 23 ]. Most prognostic tools were derived from cohort studies, with the exceptions being registries [ 29 , …”
Section: Resultsmentioning
confidence: 99%
“…There is even a greater paucity of data-driven scientific reports on the pattern of sICH in LMIC. We are aware of only one or so ( 25 ). Yet, there is increasing empirical evidence that the incidence and frequency of sICH in these regions are much higher than in the west; 29–60% versus 16–20% ( 4 , 5 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the existing ICH scores were mainly designed for short-term (in-hospital or 30 days after ICH) [6-8,10,13-16] or intermediate-term (three months after ICH) [9,11] outcome prediction. Studies have shown that a substantial proportion of ICH patients continue to improve throughout the first year after ICH [17].…”
Section: Introductionmentioning
confidence: 99%